BIOTRANSFORMATION OF trans-CINNAMALDEHYDE BY THE FILAMENTOUS FUNGUS Aspergillus sp. - VELASCO B., Rodrigo; ARISTIZABAL, Diego A.; GARCÍA P., Carlos M.; GIL G., Jesús H.; DURANGO R., Diego L. (Vitae, 2010)
The development of biocatalytic methods has allowed the preparation of a wide variety of products with high added value through simple, selective, economical and environmentally friendly processes. In this work, the microbial transformation of arylpropanoide substrate trans-cinnamaldehyde using the fungus Aspergillus sp. was investigated. The process is carried out in liquid media culture Sabouraud y Czapeck- Dox to an average temperature 24oC, relative humidity between 45 and 60%, and with agitation at 120 rpm on a orbital shaker. The biotransformation of the substrate generated mainly the metabolic products 3-phenyl-1-propanol, cinnamyl alcohol, 3-phenylpropanal, 3-phenylpropyl acetate, cinnamyl acetate,benzylic alcohol, 1-phenylethanol, and 2-phenylethanol. From the results it is concluded that the fungus Aspergillus sp. initially converted the trans-cinnamaldehyde by reduction reactions, and later modified the products resulting through esterification and decarboxylation. In the process, several compounds used as raw materials in different industries were generated. The metabolic pathway and culture medium effect on substrate transformation are discussed.